Inflation in Low-Income Countries - Ha, Jongrim; Ivanova, Anna; Montiel, Peter; Pedroni, Peter (World Bank, Washington, DC, 2019)
This paper studies the effects of global and domestic inflation shocks on core price inflation in 105 countries between 1970 and 2016, by using a heterogeneous panel vector-autoregressive model. The methodology allows accounting for differences across groups of countries (advanced economies, emerging markets and developing economies, and low-income countries) and across groups with different country characteristics (such as foreign exchange and monetary policy regimes). The empirical results indicate that most of the variation in inflation among low-income countries over the past decades is accounted for by external shocks. More than half of the variation in core inflation rates among low-income countries is due to global core price shocks, compared with one-eighth in advanced economies. Global food and energy price shocks account for another 13 percent of core inflation variation in low-income countries -- half more than in advanced economies and one-fifth more than in emerging markets and developing economies. This points to challenges in anchoring domestic inflation expectations, which have been most evident among low -- income countries with floating exchange rates, especially in cases where central bank independence has been weak.